Search for flavour-changing neutral-current couplings between the top quark and the Higgs boson in multi-lepton final states in 13 TeV pp collisions with the ATLAS detector - Aad, G; Aakvaag, E; Abbott, B; Abeling, K; Abicht, NJ; Abidi, SH; Aboelela, M; Aboulhorma, A; Abramowicz, H; Abreu, H; Abulaiti, Y; Acharya, BS; et al. (SpringerOpen, 2024)
A search is presented for flavour-changing neutral-current interactions involving the top quark, the Higgs boson and an up-type quark (q=u, c) with the ATLAS detector at the Large Hadron Collider. The analysis considers leptonic decays of the top quark along with Higgs boson decays into two W bosons, two Z bosons or a τ+τ- pair. It focuses on final states containing either two leptons (electrons or muons) of the same charge or three leptons. The considered processes are tt¯ and Ht production. For the tt¯ production, one top quark decays via t→Hq. The proton–proton collision data set analysed amounts to (140fb-1) at (s=13TeV). No significant excess beyond Standard Model expectations is observed and upper limits are set on the t→Hq branching ratios at 95 % confidence level, amounting to observed (expected) limits of B(t→Hu)<2.8(3.0)×10-4 and B(t→Hc)<3.3(3.8)×10-4. Combining this search with other searches for tHq flavour-changing neutral-current interactions previously conducted by ATLAS, considering H→bb¯ and H→γγ decays, as well as H→τ+τ- decays with one or two hadronically decaying τ-leptons, yields observed (expected) upper limits on the branching ratios of B(t→Hu)<2.6(1.8)×10-4 and B(t→Hc)<3.4(2.3)×10-4.